Bridging the Gender Wage Gap: Gendered Cultural Sentiments, Sex Segregation, and Occupation-Level Wages. (June 2020) - Freeland, Robert E.; Harnois, Catherine E.
The extent to which cultural beliefs about gender shape occupation-level wages remains a central yet unresolved question in the study of gender inequality. Human capital theorists predict that gendered beliefs have no direct effect on occupation-level wages. Devaluation theorists argue that occupations associated with women and femininity are systematically devalued and thus underpaid. We test these explanations using data from the American Community Survey, the Occupational Information Network, and an affect control theory (ACT) data set of affective meanings. We use the ACT data set to operationalize occupational gendered cultural sentiments along two distinct dimensions: evaluation (goodness, caring, warmth) and potency (power, strength, competence). Hierarchical linear models show that potency but not evaluation affects occupational income net of individual and occupational controls. Path analyses show that potency has a direct effect net of occupational traits. The gender composition of an occupation indirectly affects occupational income through potency. The cultural meanings of potency/competence associated with masculinity, rather than the devaluation of feminine nurturant occupations, is the primary cultural mechanism linking gender composition and occupational reward.